A Mini-Review of the Medicinal Properties of Okra (Abelmoschus esculentus L.) and Potential Benefit against SARS-CoV-2 - Arif Nur Muhammad Ansori (Indian Journal of Forensic Medicine & Toxicology, 2021)
Indonesia is rich in medicinal plants, where its population has traditionally used them for generations tocure diseases. Traditional medicine and medicinal plants from Indonesia may lead to the discovery of noveldrugs. Abelmoschus esculentus L. or okra is well known as a cure for several diseases and is includedin various folk medicinal stockpiles. In recent decades, scientists have discovered the phytochemicalcomposition in the whole okra plant, as well as its pharmacological activities. These studies establishedthe therapeutic potential of okra for drug discovery. Therefore, the present review provides a sneak peek ofokra’s pharmacology and phytochemistry, also the potential benefit against SARS-CoV-2.